واقع إستخدام التعليم الإفتراضى والتعليم النقال فى برامج التعليم عن بعد على ضوء بعض خبرات وتجارب عربية وعالمية - عزة شحاتة (Journal of Distance Learning and Open Learning, 2016)
The tremendous developments in information and communication technology has led to the emergence of modern electronic educational resources, which swept various fields appeared the so-called the virtual learning and virtual classroom and virtual university and e-learning and open learning, and education Built, and learning mobile, digital library, and applications of the third generation of the Web, all stemming from distance learning programs, studies and scientific research has proved its effectiveness in education and training, Although these changes and technical developments in contemporary societies today have become a strain on the educational field, so the calls appeared in the media intelligentsia logical response to the challenges arising from the rapid scientific change and technology in higher education institutions and the public to find alternatives to put educational opportunities are more accessible and spacious and comes on top of that alternatives and these developments virtual learning, which is quick and distinctive way that provides a virtual learning environment for learners meet their needs beyond the limits of time and space, Virtual classrooms is one of the new technologies that emerged from the "idea of ​​a combination of distance learning and e-learning and virtual learning, also helped the rapid growth in recent years in the mobile hardware technologies; and of increasing the capacity of the infrastructure network structure Broadband, and advances in wireless networking technologies , and the prevalence of the use of mobile phones and the evolution of its industry to discover new horizons allowing to take advantage of them in education appeared a new concept of learning is mobile; which is a new form of education systems remotely, and the pattern of a learning electronically unique complement to the process of education, calls for the use of means of technical and portable devices Modern in learning, to provide a new type of education, fit changing circumstances and current developments created by globalization, and commensurate with the characteristics and needs of learners and their courses of study.   The main objective of this research: the knowledge of The reality of use the virtual learning and Mobile Learning in distance Learning programs in the light of the experiences of some Arab and international experiences, and the branches of this main goal the following objectives: 1- Know what the virtual learning and Mobile Learning in distance Learning programs , and the most prominent characteristics.  2-knowledge of the importance of the use of the virtual learning and Mobile Learning in distance learning programs. 3-Knowledge of The relationship between the virtual learning and Mobile Learning and other learning environments. 4- The main obstacles and challenges facing the virtual learning and Mobile Learning in distance learning programs.    Methodology: The following descriptive approach and method for the study of this phenomenon, and analyze the results of previous studies and research, and access to some Arab and international experiences in the application the virtual learning and Mobile Learning  the results the virtual learning and Mobile Learning are evolving formula for distance education, there are some challenges and obstacles that continue to pose one of the inherent features of the virtual learning and Mobile Learning in distance learning programs, along with a need mobile learning to infrastructure and networks for wireless and modern devices        Recommendations: Emphasize the importance of the virtual learning and Mobile Learning and their ability in the educational process, the fact that this type of education serves the many segments of society, away from the limits of space and time limitations, Unify Arab efforts to develop distance learning programs and environments virtual learning and  Mobile Learning and the development of University curricula electronic, employment of distance Learning programs in university education partially, so that it is teaching some university courses distance Learning system.